Mitochondrial puzzle in muscle: Linking the electron transport system to overweight - Casuso, Rafael A. (Obesity reviews, 2024)
Summary Human skeletal muscle mitochondria regulate energy expenditure. Research has shown that the functionality of muscle mitochondria is altered in subjects with overweight, as well as in response to nutrient excess and calorie restriction. Two metabolic features of obesity and overweight are (1) incomplete muscular fatty acid oxidation and (2) increased circulating lactate levels. In this study, I propose that these metabolic disturbances may originate from a common source within the muscle mitochondrial electron transport system. Specifically, a reorganization of the supramolecular structure of the electron transport chain could facilitate the maintenance of readily accessible coenzyme Q pools, which are essential for metabolizing lipid substrates. This approach is expected to maintain effective electron transfer, provided that there is sufficient complex III to support the Q‐cycle. Such an adaptation could enhance fatty acid oxidation and prevent mitochondrial overload, thereby reducing lactate production. These insights advance our understanding of the molecular mechanisms underpinning metabolic dysregulation in overweight states. This provides a basis for targeted interventions in the quest for metabolic health.